Risk management in the transition strategy to a shared services center: perception of the collaborators of a transnational company - Robledo Martínez, Juan Heriberto (2022)
Shared service centers are a business model that makes operations more efficient, locating geographically in strategic places. Understand the global vision of an organization regarding the risks in the transition of a shared service center, know the way in which the implementation of the risk management process has been developed in accordance with international standards and analyze the way in which it is integrates strategic management to risk management processes, are the objectives of this work. For this, the perspective of the CoE collaborators was collected through a survey. The results reveal that the concept of risks and their management are widely known in the organization and there is a control environment that allows mitigating most of the risks that arise, since the organization is aligned with the guidelines issued by the COSO and ISO-31000 by adapting its own framework and robust platform as part of its risk management strategy. The main contribution of this work is to show the way in which a leading company in the industry carried out risk management in the transition of the operations of its countries to the shared services center.